The German TEIQue-SF: Factorial structure and relations to agentic and communal traits and mental health. (January 2015) - Jacobs, Ingo; Sim, Chu-Won; Zimmermann, Julia
Highlights: The TEIQue-SF fitted to the higher-order factor structure suggested by TEI theory. Agency and Communion related positively to TEI and negatively to IMHDs. Both unmitigated traits related negatively to TEI and positively to IMHDs. TEI mediated the impact of the agentic and communal traits on IMHDs. Abstract: Recent research illuminated the links between Agency, Communion, trait emotional intelligence (TEI), and internalizing mental health difficulties (IMHDs). However, for a more complete picture, unmitigated Agency and Communion have also to be considered. Drawing on a sample of N = 405 female occupational therapists, the present study examined (a) the factorial validity of the German TEI Questionnaire Short Form, (b) the relations of TEI to Agency, Communion, and their unmitigated variants, and (c) a multiple predictor-TEI-IMHDs mediation model. The factor structure suggested by TEI theory fitted approximately to the data. Agency and Communion related positively and both unmitigated traits related negatively to TEI. Indirect effects via TEI on IMHDs emerged for all four traits. The results help to integrate TEI within the Agency–Communion framework and suggest that TEI is an important intervening variable that helps to clarify the links of agentic and communal traits to mental health.